Crucial role of nucleic acid sensing via endosomal toll-like receptors for the defense of streptococcus pyogenes in vitro and in vivo - Hafner, Anna; Kolbe, Ulrike; Freund, Isabel; Poth, Tanja; Weigand, Markus A.; Dalpke, Alexander; Eigenbrod, Tatjana (Frontiers in immunology, 2019)
Streptococcus pyogenes is a major human pathogen causing a variety of diseases ranging from common pharyngitis to life-threatening soft tissue infections and sepsis. Microbial nucleic acids, especially bacterial RNA, have recently been recognized as a major group of pathogen-associated molecular patterns (PAMPs) involved in the detection of Streptococcus pyogenes via endosomal Toll-like receptors (TLRs) in vitro. However, the individual contribution and cooperation between TLRs as well as cell-type and strain specific differences in dependency on nucleic acid detection during S. pyogenes infection in vitro have not been clarified in detail. Moreover, the role of particularly bacterial RNA for the defense of S. pyogenes infection in vivo remains poorly defined. In this study, we report that in all investigated innate immune cells involved in the resolution of bacterial infections, including murine macrophages, dendritic cells and neutrophils, recognition of S. pyogenes strain ATCC12344 is almost completely dependent on nucleic acid sensing via endosomal TLRs at lower MOIs, whereas at higher MOIs, detection via TLR2 plays an additional, yet redundant role. We further demonstrate that different S. pyogenes strains display a considerable inter-strain variability with respect to their nucleic acid dependent recognition. Moreover, TLR13-dependent recognition of S. pyogenes RNA is largely non-redundant in bone marrow-derived macrophages (BMDMs), but less relevant in neutrophils and bone marrow-derived myeloid dendritic cells (BMDCs) for the induction of an innate immune response in vitro. In vivo, we show that a loss of nucleic acid sensing blunts early recognition of S. pyogenes, leading to a reduced local containment of the bacterial infection with subsequent pronounced systemic inflammation at later time points. Thus, our results argue for a crucial role of nucleic acid sensing via endosomal TLRs in defense of S. pyogenes infection both in vitro and in vivo.
Gesehen am 24.07.2019